The long-term effects of reproductive health education among primary and secondary school students: a longitudinal quasi-experimental study in rural Tanzania - Yoko Shimpuku; Naoki Hirose; Sanmei Chen; Dorkasi L. Mwakawanga; Niko Madeni; Frida Madeni; Mariko Komada; Ayaka Teshima; Mayu Morishima; Yasunobu Ando; Koji Takahama; Atsushi Nishida (Reproductive Health, 2023)
Abstract Background Adolescent pregnancy remains a major global health issue, increasing the risk of complications during pregnancy and childbirth in mothers and babies. In Tanzania, adolescent pregnancy threatens girls’ education and makes it difficult for them to obtain a proper job; hence, the majority fall into poverty. Previous studies have developed and conducted reproductive health education for adolescent students; however, they evaluated only the effect immediately after education. Therefore, this study investigated the effects of reproductive health education on attitudes and behaviors toward reproductive health among adolescent girls and boys one year after the intervention in rural Tanzania. Methods A longitudinal quasi-experimental study was conducted with 3295 primary and secondary students (2123 in the intervention group, 1172 in the control group) from three purposefully selected wards in Korogwe District. In the intervention group, the students received reproductive health education. We used paper-based questionnaires to evaluate the effect of the adolescent education program on attitudes and behaviors toward reproductive health education. To analyze the association between the intervention and each outcome, mixed-effect multiple regression analyses was conducted. Results The mean age, primary school proportion, and female proportion of the intervention and the control group was 13.05 (standard deviation (SD) 1.59), 14.14 (SD 1.7), 77.9% and 34.3%, and 54.2% and 52.6%, respectively. There was no statistically significant effect of reproductive health education on adolescent health attitudes and behaviors in the multiple regression analyses (coefficient: − 0.24 (95% confidence interval (CI): − 0.98 to 0.50), coefficient: 0.01 (95%CI: − 0.42 to 0.43)). Conclusion A statistically significant effect of reproductive health education on adolescent health attitudes and behaviors was not found. An effective reproductive health education intervention to improve the attitude and behaviors of reproductive health among Tanzania adolescents in the long term remain to be determined, particularly in real-world settings. Trial registration The National Institute for Medical Research, Tanzania (NIMR/HQ/R.8a/Vol. IX988).